2011
DOI: 10.5402/2011/282361
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Laser Surgery and Prosthetic Management for the Treatment of Epulis Fissuratum

Abstract: The aim of this study was to present a case report of the surgical removal of hyperplasia in the oral cavity, using carbon dioxide (CO2) laser radiation and rehabilitation with a complete denture. Epulis fissuratum occurs in complete denture patients, because a constant irritative action induces the mucosa to grow under poorly fitting dentures. These lesions must be removed, and to avoid a relapse, new complete dentures should be made to maintain healthy surgical tissues. The clinical sequence presented in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
(13 reference statements)
0
5
0
5
Order By: Relevance
“…de Arruda Paes-Junior et al and also Suter et al reported significant low amount of bleeding in excisional biopsy by CO 2 laser without suturing. 8,9 Our findings showed that the bleeding was lower with CO 2 laser compared to surgery with scalpel. Fisher and Frame reported reduction in vestibular depth in fibro epithelial hyperplasia surgery.…”
Section: Discussionmentioning
confidence: 54%
“…de Arruda Paes-Junior et al and also Suter et al reported significant low amount of bleeding in excisional biopsy by CO 2 laser without suturing. 8,9 Our findings showed that the bleeding was lower with CO 2 laser compared to surgery with scalpel. Fisher and Frame reported reduction in vestibular depth in fibro epithelial hyperplasia surgery.…”
Section: Discussionmentioning
confidence: 54%
“…In contrast to sharp excision, laser excision of the epulis fissuratum results in minimal bleeding and reduced post-operative pain. Surgery is faster because the wound does not require suturing, and scarring is minimal 12 . While the laser offers many benefits, special equipment is needed and may not be readily available in a given setting.…”
Section: Discussionmentioning
confidence: 99%
“…"Al examen clínico se observó una lesión hiperplásica sobre la cresta alveolar con extensión hasta el surco vestibular en la parte inferior de la región anterior mandibular". 14 Estas lesiones fueron eliminadas con láser de CO2 y los resultados fueron una reparación satisfactoria del tejido después de siete días sin formación de cicatrices, luego se procedió a elaborar una nueva prótesis con un adecuado ajuste y sin recidiva a 30 días de seguimiento 14 .De igual forma Kumar y Bhaskaran 15 reportaron un caso de una mujer de 70 años de edad que presentaba una lesión fibrosa alargada de la mucosa oral en la zona vestibular del maxilar, la misma que fue tratada con láser de CO2. Los resultados fueron una adecuada cicatrización y no hubo recidiva a dos años de seguimiento.…”
Section: Terapia Láserunclassified
“…Sin embargo existen estudios en los que se hace referencia a casos de recidiva posterior al manejo quirúrgico con bisturí. 14 Eroglu y col. 16 realizaron 44 cirugías de eliminación de épulis fissuratum en 30 voluntarios sanos y determinaron que la cirugía a bisturí produce mayor dolor postoperatorio en comparación con el láser (Erbio, Cromo: Ytrio-Escandio-Galio-Granate).…”
Section: Terapia Quirúrgica Convencionalunclassified